Physiological Perspectives on Molecular Mechanisms and Regulation of Vesicular Glutamate Transport: Lessons From Calyx of Held Synapses - Hori, Tetsuya; Takamori, Shigeo (Frontiers in Cellular Neuroscience, 2022)
Accumulation of glutamate, the primary excitatory neurotransmitter in the mammalian central nervous system, into presynaptic synaptic vesicles (SVs) depends upon three vesicular glutamate transporters (VGLUTs). Since VGLUTs are driven by a proton electrochemical gradient across the SV membrane generated by vacuolar-type H+-ATPases (V-ATPases), the rate of glutamate transport into SVs, as well as the amount of glutamate in SVs at equilibrium, are influenced by the activity of both VGLUTs and V-ATPase. Despite emerging evidence that suggest various factors influencing glutamate transport by VGLUTs in vitro, little has been reported in physiological or pathological contexts to date. Historically, this was partially due to a lack of appropriate methods to monitor glutamate loading into SVs in living synapses. Furthermore, whether the speed of glutamate refilling of SVs can be rate-limiting for synaptic transmission is not well understood, primarily due to a lack of knowledge concerning the time required for vesicle reuse during repetitive stimulation. In this review, we first introduce a unique electrophysiological method to monitor glutamate refilling by VGLUTs in a giant model synapse from the calyx of Held in rodent brainstem slices, and we discuss advantages and limitations of the method. We then introduce current understanding of factors that potentially alter the amount and rate of glutamate refilling of SVs in this synapse, and discuss open questions from physiological viewpoints.